THE EFFECT OF ADDITION OFCATFISH SURIMI (Pangasius hypopthalmus) AS A SOURCE OF PROTEIN ON THE QUALITY OF TORTILLA CHIPS (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aimed to find out the effect of the addition of surimi catfish (Pangasius hypopthalmus) andto determine the percentage of the best surimi formulations as a source of protein to the quality of trortilla chips. The research method used is an experimental and composed for non-factorial Complete Randomized Design consisted of 4 levels (0, 5%, 10%, and 15 % catfishsurimi added). The results showed thatthe addition of surimi catfish 15% was indicating the best concentrationcatfishsurimi. The product wascharacterized by the whole, attractive, yellow golden appearance(7.47), specific aromas of strong tortilla chips (6.93), very savory taste, very specific flavor of tortilla chips (7.52), and crunchy texture (6.63). The proximate composition containing the moisture of 4.07%, ash of 3.91%, and protein of 21.07%.Keywords: Catfish, Surimi, Tortilla Chips